2019
DOI: 10.1126/sciadv.aaw8651
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Gag specifically restricts PI(4,5)P2 and cholesterol mobility in living cells creating a nanodomain platform for virus assembly

Abstract: HIV-1 Gag protein assembles at the plasma membrane of infected cells for viral particle formation. Gag targets lipids, mainly PI(4,5)P2, at the inner leaflet of this membrane. Here, we address the question whether Gag is able to trap specifically PI(4,5)P2 or other lipids during HIV-1 assembly in the host CD4+ T lymphocytes. Lipid dynamics within and away from HIV-1 assembly sites were determined using super-resolution microscopy coupled with scanning fluorescence correlation spectroscopy in living cells. Anal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 67 publications
1
72
1
Order By: Relevance
“…Lipidomic studies provided clear evidence that the lipid composition of the viral envelope differs from that of the plasma membrane of producer cells [2][3][4][5]. The enrichment in sphingomyelin and cholesterol suggests that HIV buds from specialised nanodomains in the plasma membrane, as previously evidenced [6] and further confirmed [7,8]. In particular, cholesterol proved to be a critical lipid, since its depletion from virions inhibits HIV infectivity [9][10][11].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Lipidomic studies provided clear evidence that the lipid composition of the viral envelope differs from that of the plasma membrane of producer cells [2][3][4][5]. The enrichment in sphingomyelin and cholesterol suggests that HIV buds from specialised nanodomains in the plasma membrane, as previously evidenced [6] and further confirmed [7,8]. In particular, cholesterol proved to be a critical lipid, since its depletion from virions inhibits HIV infectivity [9][10][11].…”
Section: Introductionmentioning
confidence: 54%
“…Recent microscopy studies on live cells confirmed that Gag recruits proteins and lipids at budding platforms [7,8]. Super-resolution experiments (stimulated emission depletion (STED) microscopy in combination with fluorescence correlation spectroscopy (FCS), STED-FCS) in HIV-infected cells proved that fluorescent analogues of cholesterol (labelled with Abberior STAR RED via a PEG-linker) and PIP 2 (PIP(4,5) 2 labelled with ATTO647N) were trapped at Gag assembly sites, as opposed to fluorescent analogues of sphingomyelin (SM, labelled with ATTO647N) and phosphoethanolamine (DPPE, labelled with ATTO647N or Abberior STAR RED) ( Figure 1) [8]. Gag-induced lipid platforms were independently detected at the plasma membrane of transfected cells [7], which were enriched in fluorescent analogues of cholesterol, ganglioside GM1, SM (all TF-labelled) ( Figure 1), and glycophosphatidylinositol (GPI) anchored proteins (labelled with enhanced green fluorescent protein (EGFP)).…”
Section: Imaging Lipids During Hiv Assembly and Buddingmentioning
confidence: 99%
“…This system has allowed easy tracking and observation of multiple rounds of ESCRT recruitment in the same VLP. Observing multiple rounds of assembly during HIV budding in T-cells remains technically out of reach, due to the limited membrane and cellular movements of T-cells [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…More recently the brightness distribution was used within the cytosol to detect the state of oligomerization of Gag during HIV budding [ 89 ]. A combination of STED and scanning FCS was also used to detect the dynamics of PIP2 during early stages of HIV assembly [ 90 , 91 ]. Fluctuation spectroscopy therefore offers both measurements of dynamics as well as status of molecular aggregates which can be very informative for the study of HIV budding and maturation.…”
Section: Application Of Fluctuation Spectroscopy To Hiv Biologymentioning
confidence: 99%